Electrochemical Oxidation of Metal Carbides in Aqueous Solutions. Issue 4 (1st January 2018) - Messner, Matthew; Walczyk, Dustin J.; Palazzo, Benjamin. G.; Norris, Zachary A.; Taylor, Gregory; Carroll, John; Pham, Tung X.; Hettinger, Jeffrey D.; Yu, Lei
Abstract : Transition metal carbides have unique properties such as high hardness, high melting temperatures, high thermal conductivity, and high chemical stability. In this report, we investigate the electrochemical oxidation of a series of metal carbides including NbC, Nb2 C, TaC, Ta2 C, VC, VCrC, TiC and TiCrC in neutral, basic, or acidic aqueous solutions. Cyclic voltammetry and elemental analysis demonstrated that many of these metal carbides can be electrochemically oxidized at low electrode potentials to produce soluble metal ions in the solutions. Carbon in the metal carbides remains on the electrode substrates and forms porous carbide-derived carbon (CDC). The surface morphology of the CDC and specific surface area depend on the metal carbide precursors and the electrochemical oxidation conditions.